2010
DOI: 10.1016/j.juro.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Evaluation of Periureteral Botulinum Toxin Type A Injection for Ureteral Stent Pain Reduction

Abstract: Periureteral botulinum toxin type A injection improves ureteral stent tolerability by significantly decreasing postoperative pain and narcotic requirements. Improvement in irritative symptoms was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…55 This randomized, single-blind study showed a significant decrease in pain and less narcotic use in the treated group, whereas none of the USSQ subscores improved.…”
Section: Intravesical Instillations or Injectionsmentioning
confidence: 82%
“…55 This randomized, single-blind study showed a significant decrease in pain and less narcotic use in the treated group, whereas none of the USSQ subscores improved.…”
Section: Intravesical Instillations or Injectionsmentioning
confidence: 82%
“…If a ureteral stent is needed after endoscopic surgery, ureteral length should be measured so that an appropriate stent can be used in patients, which can reduce distal migration and stent-related symptoms [10]. Periureteral injection of botulinum toxin type A after stent insertion has been shown to decrease pain and narcotic requirement [11]. …”
Section: Discussionmentioning
confidence: 99%
“…If a ureteral stent is needed after endoscopic surgery, ureteral length should be measured so that an appropriate stent can be used in patients, which can reduce distal migration and stent-related symptoms [10]. Periureteral injection of botulinum toxin type A after stent insertion has been shown to decrease pain and narcotic requirement [11]. We believe that new stent development is difficult.…”
Section: Discussionmentioning
confidence: 99%